Internal Model Loss Minimization Control of Permanent Magnet Synchronous Machine (Nigerian Journal of Technology, 2021)
Electric drives are very useful in propelling the wheels of hybrid electric vehicles (HEVs). They also play a central function in the electric power steering (EPS). This paper describes studies carried out on the efficiency optimization of an interior permanent magnet synchronous machine (IPMSM) for application in the EPS. An analytic loss-minimization algorithm for an IPMSM was derived and the optimization problem took into consideration copper, iron and stray losses. The proposed loss minimization algorithm is simple and cost effective to implement. From the simulations carried out, significant efficiency gains are possible with this model. The internal model control (IMC) method was employed to achieve current and speed control with acceptable sensitivity to machine parameters.http://dx.doi.org/10.4314/njt.v40i1.14